Observer-Based Novel Fuzzy Dynamic Output-Feedback Tracking Control for Discrete-Time Systems - Yang Wang; Xiaolei Ji (IEEE Access)
This paper delves into the realm of observer-centric tracking control for discrete-time nonlinear networked control systems, accounting for packet dropouts and addressing the issue of state variables that are not directly measurable. To tackle this, an innovative fuzzy observer independent of premise variables is devised. A key innovation lies in the introduction of a new fuzzy observer that compensates for unmeasurable states, utilizing the system’s dynamic output to achieve more precise estimation results. The observer employs both the error between the measurable output of the system and the observer’s estimate, as well as the error between the system’s measurable output and the reference model’s output, as compensation mechanisms. Furthermore, in harmony with the controller, the observer adopts a regulatory factor structure and utilizes the same membership functions as the controller, thereby achieving a less conservative design. Subsequently, a novel fuzzy tracking controller is meticulously proposed, leveraging the estimates provided by the observer. Moreover, sufficient criteria are formulated to ensure that the resulting closed-loop system attains stochastic stability. Finally, to underscore the practical effect of our approach, illustrative examples are presented.